Realistic assessment of irrigation potential in the Lake Tana basin, Ethiopia - Wale, A.; Collick, A.S.; Rossiter, D.G.; Langan, Simon J.; Steenhuis, Tammo S. (International Livestock Research Institute, 2013)
Although Ethiopia has a large potential to develop irrigation, only 5% of the 3.5 million hectares of land potentially available has been developed. To examine the underlying causes, this study evaluates the suitability of surface water irrigation for the Lake Tana Basin development corridor. Surface water availability and land potentially suitable for medium and large-scale irrigation development (200 ha and larger) was considered. Surface water potential was examined by considering river discharges. Land suitable for irrigation was determined with a GIS-based multi-criteria evaluation (MCE), which considers the interaction of various factors, such as climate, river proximity, soil type, land cover, topography/slope and market outlets. The result indicates that nearly 11% of the Lake Tana Basin is suitable for surface irrigation. However, by analysing 27 years of river discharge, less than 3% of the potential irrigable area (or less than 0.25% of the basin area) could be irrigated consistently by run-of-the river-systems. Thus, the irrigation potential in the Lake Tana Basin can only be met by increasing dry season flows (if proven feasible) and by supplying water from existing or future reservoirs or by using water directly from Lake Tana.